2021
DOI: 10.1002/jcc.26779
|View full text |Cite
|
Sign up to set email alerts
|

Improving ligand‐ranking of AutoDock Vina by changing the empirical parameters

Abstract: AutoDock Vina (Vina) achieved a very high docking‐success rate, truep^, but give a rather low correlation coefficient, R, for binding affinity with respect to experiments. This low correlation can be an obstacle for ranking of ligand‐binding affinity, which is the main objective of docking simulations. In this context, we evaluated the dependence of Vina R coefficient upon its empirical parameters. R is affected more by changing the gauss2 and rotation than other terms. The docking‐success rate truep^ is sensi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…In particular, the ligand-binding pose was delivered by molecular docking simulations instead of experimental data. 22 The equilibrated conformation of the complex could be effectively obtained using unbiased MD simulations. 91 Moreover, a previous benchmark indicated that SMD simulations provided more accurate results when the initial conformation was the MD-refined structure.…”
Section: Computational Methods and Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the ligand-binding pose was delivered by molecular docking simulations instead of experimental data. 22 The equilibrated conformation of the complex could be effectively obtained using unbiased MD simulations. 91 Moreover, a previous benchmark indicated that SMD simulations provided more accurate results when the initial conformation was the MD-refined structure.…”
Section: Computational Methods and Applicationsmentioning
confidence: 99%
“…The metric can be determined via computation, and several methods have been established to solve the issues. 21 Numerous physics-based approaches have been designed, such as molecular docking simulations, 22,23 linear interaction energy (LIE), 24 fast pulling ligand (FPL), 25 molecular mechanics-Poisson–Boltzmann (generalized Born) surface area (MM-PB(GB)SA), 26,27 nonequilibrium molecular dynamics (NEMD), 28 thermodynamic integration, 29 free energy perturbation (FEP), 30 replica-exchange free energy perturbation (REP) 20 methods, etc. Moreover, knowledge-based methods also play a crucial role in estimating the binding affinity of a ligand to a protein, such as the quantitative structure–activity relationship (QSAR) 31,32 or machine learning (ML) methods.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular docking simulations were usually performed to preliminary probe the binding affinities and poses of the ligands to receptors. 57,58 In this work, AutoDock Vina with the modified empirical parameters 43 was executed to explore the ligand-binding pose and affinity to N1. Initially, a benchmark was carried out to assess the performance of the docking protocol.…”
Section: Resultsmentioning
confidence: 99%
“…AutoDock VINA 58 (version 1.1.2) was used to obtain and investigate binding site predictions. While docking programs in general are great tools for determining the geometric orientation or pose of a ligand in a binding site, the correlation coefficient of the docking score returned by AutoDock VINA and the experimental binding affinity is rather limited (≈0.493) 59,60 but comparable to other docking programs. 60 Due to the large extent of the K35/K85 keratin heterodimer and the presence of charged residues in its sequences, it is expected that more than a single site per heterodimer will be found.…”
Section: Human Hair Keratin Heterodimermentioning
confidence: 99%
“…AutoDock VINA (version 1.1.2) was used to obtain and investigate binding site predictions. While docking programs in general are great tools for determining the geometric orientation or pose of a ligand in a binding site, the correlation coefficient of the docking score returned by AutoDock VINA and the experimental binding affinity is rather limited (≈0.493) , but comparable to other docking programs …”
Section: Theory and Computational Detailsmentioning
confidence: 99%